New Challenge, New Motivation? Goal Orientation Development in Graduates of Higher Track Schools and Their Peers in Vocational Training - Becker, Sarah; Pfost, Maximilian; Artelt, Cordula (Frontiers in Psychology, 2018)
Many studies have demonstrated a decrease in mastery-approach goals and an increase in performance-approach goals after students’ transition from primary to secondary education. A theoretical explanation for this phenomenon is a deteriorating fit between a learner’s needs and environmental conditions. The purpose of this study was to further examine the development of students’ goal orientation after they graduated from a higher track secondary school and transitioned to university or vocational training as compared with peers who chose vocational training earlier. We also examined the fit between the students’ needs and the conditions in the new educational context to elaborate on the differential fit hypothesis. Data from 487 students and trainees who participated in a German longitudinal school study were available for our analyses. Latent change score models indicated a significant increase in mastery-approach and a decrease in performance-approach goals for higher track graduates after they transitioned to a new educational context, paralleled by an adequate fit between the learners’ needs and the new educational context. For their peers who started vocational training early, mastery-approach goals seem to remained stable, whereas performance-approach goals decreased over time. The results are discussed in the context of the stage-environment fit theory.